2022
DOI: 10.1177/15353702221116592
|View full text |Cite
|
Sign up to set email alerts
|

Selenoproteins and the senescence-associated epitranscriptome

Abstract: Selenium is a naturally found trace element, which provides multiple benefits including antioxidant, anticancer, and antiaging, as well as boosting immunity. One unique feature of selenium is its incorporation as selenocysteine, a rare 21st amino acid, into selenoproteins. Twenty-five human selenoproteins have been discovered, and a majority of these serve as crucial antioxidant enzymes for redox homeostasis. Unlike other amino acids, incorporation of selenocysteine requires a distinctive UGA stop codon recodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…We also assessed the effects of SHS on the percentage of p21-labeled cells, an early cellular marker of senescence [ 41 ] that is upregulated in bronchial cells after exposure to cigarette smoke [ 42 ]. Nuclear staining of p21-labeled cells was more prominent in larger cells of the prefrontal cortex ( Figure 5 A) and CA1 hippocampal neurons ( Figure 5 B) of SHS-exposed mice than in sham-exposed mice.…”
Section: Resultsmentioning
confidence: 99%
“…We also assessed the effects of SHS on the percentage of p21-labeled cells, an early cellular marker of senescence [ 41 ] that is upregulated in bronchial cells after exposure to cigarette smoke [ 42 ]. Nuclear staining of p21-labeled cells was more prominent in larger cells of the prefrontal cortex ( Figure 5 A) and CA1 hippocampal neurons ( Figure 5 B) of SHS-exposed mice than in sham-exposed mice.…”
Section: Resultsmentioning
confidence: 99%
“…From these analyses, we identified the tRNA-methyltransferase AlkBH8 as a potential novel therapeutic target in CRC, as high AlkBH8 expression correlates with decreased overall survival in CRC patients (Figure 5A-B). AlkBH8 has been extensively reported to regulate the selenoproteome via methylation of tRNA-selenocysteine, with AlkBH8 knockdown and knockout models demonstrating a decreased ability to translate selenoproteins [54][55][56][57][58][59][60][61] . We observed that AlkBH8 expression is significantly increased in tumor tissue as compared to normal controls (Figure 5C), and that patients with early-onset CRC have increased expression of AlkBH8 as compared to all other age groups (Figure 5D).…”
Section: Investigating the Selenoproteome As A Therapeutic Target In ...mentioning
confidence: 99%
“…Loss of ALKBH8 and its associated methylation disrupts DNA repair and oxidative stress responses as well as cellular senescence and mitochondrial activity in mammalian cells (47)(48)(49)(50)(51)(52). ALKBH8 regulates oxidative stress via regulation of selenoprotein synthesis, which relies on methylation of tRNA-selenocysteine (tRNA Sec ) for recoding UGA stop codons.…”
Section: Introductionmentioning
confidence: 99%